USE MATHEMATICAL FORMULAS IN ELECTRONIC COMPUTING MACHINES - Gulchiroy Inomova Baxtiyor qizi, Qodirova Maloxat Komiljonovna (American Journals, 2023)
This article summarizes general information about electronic computing machines and the use of mathematical formulas in them..
Keywords: electronic computing machines, mathematical formulas, electronic devices, etc.